A microsurgical technique for catheter insertion in the rat femoral artery - Sugai, Kazuhisa (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2020)

(untitled) (Acta Cir Bras)
PURPOSE: To modify a surgical catheterization method using the bent needle introducer in small animals. METHODS: Eight-week-old male Lewis rats were used in the study. A needle introducer was created by bending a 21G injection needle at 45°. The bent needle introducer was used for catheter insertion into the left femoral artery of the rats under anesthesia. As a control, a catheter was directly inserted into the blood vessel without the introducer. The insertion time of each method was measured. Blood pressure and heart rate were measured 24 h after catheter insertion using the telemetry system. RESULTS: Using the introducer, the catheter was successfully inserted within a short time in all rats. Without the introducer, a longer duration was required for catheter insertion. The frequency of the insertion with no catheter-based errors with the introducer tended to be higher than that without the introducer. The mean arterial pressure and heart rate 24 h after catheter insertion in each group were almost the same. CONCLUSIONS: We developed a surgical catheterization method using the introducer in small animals. This could potentially reduce the frequency of the insertion with catheter-based errors and insertion time.